Exostoma dhritiae, a new sisorid catfish (Teleostei: Sisoridae) from the Brahmaputra River drainage, Arunachal Pradesh, India - Singh, Pratima; Kosygin, Laishram; Gurumayum, Shantabala Devi; Rath, Shibananda (Zootaxa, 2022)
A new species of sisorid catfish of the genus Exostoma is described from the Siang River in Arunachal Pradesh, northeastern India. The new species, Exostoma dhritiae, can be distinguished from congeners by the condition of the posterior extremity of the adipose-fin base, the degree of tuberculation on the dorsal surface of the head, and the shape of striae on the anterolateral surface of lips. Further, it is distinguished by the morphometric data for the body depth at the anus, maxillary barbel length, adipose fin base length, caudal peduncle length, caudal peduncle depth and the number of branched pectoral-fin rays. It is the twentieth reported species of Exostoma.